Muscarinic M1 and M2 receptor subtypes play opposite roles in LPS-induced septic shock - Wang, Zhen; Li, Mingyi; Liu, Lu; Geng, Bin (Pharmacological reports, 2019)
To compare pharmacologic effects of pirenzepine and AF-DX116, a selective competitive antagonist for M1 and M2 subtype muscarinic cholinergic receptors (mAChRs), respectively, with atropine, a non-selective competitive antagonist for mAChRs, on Lipopolysaccharide (LPS). Male C57BL/6 mice were used to establish models of LPS-induced experimental endotoxemia. Mice were intraperitoneally injected 10 min prior to LPS injection with control (saline), atropine, pirenzepine and AF-DX116, respectively. Overall survival time was estimated using Kaplan-Meier plots. Inflammatory cytokine tumor necrosis factor-α (TNF-α) was monitored at various intervals after LPS injection and individual reagent administration. Pathological alternations in lungs and liver were analyzed. Pirenzepine and atropine pretreatment improved survival rate of LPS-induced septic shock; in contrast, AF-DX116 accelerated death from sepsis. Moreover, TNF-α plasma level was decreased in response to pirenzepine or atropine, whereas increased in response to AF-DX116. Pirenzepine and atropine relieved whereas AF-DX116 accelerated LPS-induced pulmonary and hepatic injury. Pirenzepine reduced proportion of M1 subtype of macrophages, while AF-DX116 promoted polarization of macrophages to M1 subtype. Pirenzepine pretreatment reduced while AF-DX116 enhanced expression of SOCS3 at mRNA level. The administration of pirenzepine and atropine may have beneficial effects on septic shock.